ZONIFICACIÓN DE PERIODOS FUNDAMENTALES DEL SUELO, MEDIANTE VIBRACIONES AMBIENTALES, EN EL ÁREA CENTRO-ESTE DEL ÁREA URBANA EN LA CUENCA DE LOJA. PROVINCIA DE LOJA, ECUADOR - Pacheco Cueva, Diego Alexander (2025)
The main objective of this study is the determination of the fundamental periods of the soil over a specific area, which are an essential element to carry out seismic zoning projects in the central eastern area of the urban limit of the city, canton and province of Loja. The process began by capturing environmental vibrations using the Tromino Moho Zero seismograph, featured for its high performance and wide dynamic range. A 250m x 250m mesh was implemented to achieve an adequate representation and the same as recommended in the SESAME project, with a total of 153 measurement points with a recording time of 26 minutes. The evaluation and analysis of environmental vibrations were carried out using the method proposed by the author Nakamura (1989), which includes the determination of the horizontal and vertical spectral ratio, through the use of the Grilla software, a specialized tool for the seismograph. This approach facilitated obtaining the maximum vibration frequency and, consequently, the predominant period of the soil. As a result, the study area was divided into five categories of periods: very short, short, medium, long and very long. Additionally, a correlation was established with the geology present in the study area and, as a substantial complement, three shear wave velocities (Vs) were determined throughout the region using the Grilla software, thus deepening the analysis. The results obtained suggest that the use of environmental vibrations is an efficient alternative for the dynamic characterization of the soil, given its relative economy compared to other techniques. The information derived from this research allows the development of future studies, especially for the preparation of seismic zoning maps and in the planning of territorial developments. Keywords: Fundamental Periods of the Soil, Seismic Zoning, Environmental Soil Vibrations, Waves, Seismology.